Reducing the Negative Impact on Atmospheric Air: An Overview of Economic and Administrative and Legal Tools - Karaeva Anzhelika; Ivascu Larisa; Tolkou Athanasia K.; Kyzas George Z.; Giurea Ramona (MATEC Web of Conferences, 2024)
Solving the problem of atmospheric air pollution has been one of the most pressing topics on the modern agenda of sustainable development for more than a decade. Every day mankind emits significant amounts of greenhouse gases and toxic substances such as SO2, particulate matters, benzene, lead, etc. The low quality of atmospheric air caused by high degree of contamination entails significant negative consequences for the environment and human health in the long term. A steady increase in greenhouse gas emissions into the atmosphere provokes an increase in average temperature and, consequently, serious climate changes. Governments of different countries are developing a wide range of state programs to protect the environment and are implementing various initiatives to eco-modernize industrial enterprises that are the largest emitters of emissions. However, despite the measures taken, the situation with atmospheric air pollution remains acute in most countries of the world. The purpose of this study is to review and analyse the most common economic and administrative-legal instruments used to reduce the negative impact on atmospheric air. Based on the results of the study, the most effective tools were identified and recommendations for their further improvement were proposed.